2020
DOI: 10.1038/s41598-020-72006-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water stress on spectral reflectance of bermudagrass

Abstract: In the south-central Italy, during summer rainfall does not supply a sufficient amount of water. Therefore, irrigation management during dry periods is important for maintaining turf quality. The hybrid bermudagrass (Cynodon dactylon (L.) Pers. × Cynodon transvaalensis Burtt–Davy) is known to represent the dominant warm-season turfgrass in warm to temperate climatic regions and its drought tolerance make bermudagrass a competitive turfgrass. A greenhouse experiment was conducted using uniform cores of hybrid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…More importantly, a continuous supply of cut flowers with long vase life would benefit the horticultural industry by stimulating the cut flower popularity to consumers [16,21]. Such a candidate is the light reflectance properties, which are affected by both biochemical properties, and physiological condition [22][23][24][25][26]. The changes in cut flower reflectance during storage have not previously been evaluated, and their potential in distinguishing batches stored for different periods has not been currently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, a continuous supply of cut flowers with long vase life would benefit the horticultural industry by stimulating the cut flower popularity to consumers [16,21]. Such a candidate is the light reflectance properties, which are affected by both biochemical properties, and physiological condition [22][23][24][25][26]. The changes in cut flower reflectance during storage have not previously been evaluated, and their potential in distinguishing batches stored for different periods has not been currently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Water stressed vegetation is known to have stronger reflectance signals in visible red-light region (Adam et al, 2010;Macarthur, 1975). The study by Caturegli et al (2020) assessed the effects of water stress on spectral reflectance of Bermudagrass (Cynodon dyctolon) under controlled laboratory conditions. The results showed an increase in red light reflectance with increasing water stress, thus proving that water stressed vegetation has a stronger reflectance in the visible red-light region.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported decreases in NIR reflectance beyond 850 nm under increasing water stress [63,64,66]. Likewise, the water absorption feature around 970 nm becomes less pronounced [110]. The decrease in NIR reflectance over 900 nm exhibited by healthy archetypes is probably related to stronger water absorption in healthy vegetation.…”
Section: Archetype Classificationmentioning
confidence: 96%